Improving Student’s Motivation and Activeness in Reading Narrative Text through Character Education Values for Students Ninth Grade in SMP Negeri 9 Tambusai Utara - Zetira Ahmad (Indonesian Journal of Multidisciplinary Scientific Studies, 2024)
The main goal of learning nowadays is to increase students' motivation and activeness in learning English. The government is currently implementing a literacy habituation program to enable this character education. This study used a qualitative approach, and data were collected through observation, interview, and documentation. This research shows that students at SMP Negeri 9 Tambusai Utara (IX) are taught to read story texts through the classification of story text structures consisting of orientation, conflict, and resolution. Secondly, identifying moral values contained in the text as a whole through the search for moral values contained in the text. Narrative texts are able to give readers an extraordinary, interesting experience, and get important information. Reading the narrative test attracts students to more easily understand the moral values contained in it.